Strengthening medical abortion in South Africa - Constant, Deborah Ann (Department of Public Health and Family Medicine, 2017)
Access to safe, legal abortion services is an important public health measure to address morbidity and mortality from unsafe abortion. To expand access and strengthen medical abortion provision in South Africa, evidence is needed on the safety, effectiveness, feasibility and acceptability of task sharing strategies and the implementation of evidence-based regimens. This research aims to: (a) evaluate the safety and acceptability of task sharing gestational age estimation for women seeking abortion, (b) determine the effectiveness and acceptability of text messaging on mobile phones to support women self-managing medical abortion, (c) evaluate the feasibility, safety and acceptability of self-assessment of medical abortion completion using mobile phones alone or in combination with a low-sensitivity pregnancy test, and (d) document clinical outcomes and women's experiences following the introduction of mifepristone into second trimester medical abortion services. Published or submitted papers included in this thesis are from four prospective studies evaluating interventions and interviewing women and health care workers in South African public sector and non-governmental clinics between 2011 and 2015. The first paper establishes that last menstrual period is sufficiently accurate to estimate gestational age in selected women (97%) and has potential to be task shared with community health workers or women themselves. The second paper reports reduced anxiety (p=0.013) and better preparedness (p=0.016) for self-managing abortion symptoms among women receiving automated text messages (compared to those receiving standard care). The third and fourth papers show that mobile phones are a feasible modality for self-assessment for most women (86%), but that clinical history needs to be combined with an appropriate pregnancy test to detect incomplete or failed procedures. Self-assessment using a low-sensitivity pregnancy test is preferred by most women (98%) to in-clinic follow-up, and providing a guided demonstration on the use of a low-sensitivity pregnancy test does not significantly impact on the accuracy of self-assessed abortion outcome compared to simple verbal instructions (88% vs. 85% accuracy; p=0.449). The fifth paper documents successful self-administration of mifepristone, a higher 24-hour abortion rate (93% vs 77%; p<0.001), and greater acceptability following the introduction of mifepristone into second trimester abortion care, compared to historic cohorts receiving misoprostol only. The thesis concludes that supported self-management and task sharing can strengthen medical abortion provision in South Africa. Research evaluating task sharing of medical abortion care has potential to inform similar approaches for other health care services.